THE EFFECT OF INTERACTIVE LEARNING MEDIA ON INCREASING STUDENTS’ ENGLISH VOCABULARY AT JUNIOR HIGH SCHOOL - Nadya Fany; Nurdin Noni; Amra Ariyani (Universitas Negeri Makassar, 2026)
This study aims to find out the effect of Interactive Learning Media, specifically Quizlet, on increasing students’ English vocabulary at SMPN 19 Bulukumba. A quantitative approach was applied, using a pre-experimental design with a one-group pre-test and post-test. The sample consists of 27 eighth-grade students. Data were collected using vocabulary tests covering three aspects: word meaning, word use and word spelling. The data were analyzed using descriptive statistics, a paired sample t-test and N-Gain analysis with the assistance of SPSS version 25. The findings showed a significant improvement in students’ English vocabulary after the implementation of Quizlet. The mean score increased from 54.04 in the pre-test to 73.96 in the post-test. A paired sample t-test produced a t-value of -16.613 with a p-value of 0.000 (p < 0.05), indicating a statistically significant difference between the pre-test and post-test scores. Furthermore, the N-Gain analysis yielded an average score of 0.439, which falls into the moderate improvement category, indicating that students experienced a significant enhancement in their vocabulary. Among the three vocabulary aspects, word spelling showed the highest improvement, followed by word meaning, while word use showed a moderate increase. These findings indicate that Quizlet, as an interactive learning media is effective in increasing students’ English vocabulary at the junior high school level.